Implementation of the Law Regarding the Use of CCTV Cameras as Electronic Traffic Enforcement Tools in the City of Medan - Siti Ruqoyyah; Irwansyah Irwansyah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Closed Circuit Television (CCTV) is one of the surveillance tools that can work automatically 24 (twenty-four) which can be used as a tool that helps prevent crime on an object. This research uses a normative juridical approach method. The type of data in this study uses secondary data, and an empirical approach with a qualitative approach. The data sources used are documents and books. Secondary data is data obtained indirectly through literature studies of laws and regulations and publications of previous studies to add information, obtain a theoretical basis and legal basis. Data analysis is described qualitatively, by describing data in the form of sentences that are organized, logical, effective, so that it helps ease of understanding. This research results in the existence of CCTV (Closed Circuit Television) recording evidence recognized as valid evidence, reinforced by the issuance of the Electronic Information and Transactions Law, namely in Article 5 paragraph (1) and paragraph (2) of the ITE Law.